DOCUMENTARY READING IN THE INDEX PROCESS: possible contributions of functional linguistics - Gatto, Ana Clara [UNESP]; Martines, Alexandre Robson [UNESP]; Almeida, Carlos Candido de [UNESP] (Univ Federal Paraiba, 2023)
This article addresses the possibility of using Functional Linguistics, specifically Discursive Semantics, in document reading, a stage of the indexing process, in which Structural Linguistics is commonly used. This approach focuses mainly on structural analysis and has the word as form and meaning, while Discursive Semantics considers as key elements the semantic role that words play in discourse, making it possible to incorporate a more holistic view of the document, taking into account the communicative intention of the authors and the nuances of meaning present in the keywords. To this end, the document reading process is presented with a structuralist view, Discursive Semantics and its possible use and improvement in the indexing process with regard to the collection of keywords. It is concluded that the use of Functional Linguistics in the indexing process represents a promising alternative to the traditional approach based on the structuralist view of discourse, since incorporating the context in the definition of keywords allows for a more detailed description, in addition to considering the entire context of production.
Keywords: Documentary reading; Indexing; Functional linguistic; Discursiv semantic